Ginsenoside Rg5 enhances the radiosensitivity of lung adenocarcinoma via reducing HSP90-CDC37 interaction and promoting client protein degradation - Hansong Bai; Jiahua Lyu; Xinyu Nie; Hao Kuang; Long Liang; Hongyuan Jia; Shijie Zhou; Churong Li; Tao Li (Elsevier, 2023)
Ginsenoside Rg5 is a rare ginsenoside showing promising tumor-suppressive effects. This study aimed to explore its radio-sensitizing effects and the underlying mechanisms. Human lung adenocarcinoma cell lines A549 and Calu-3 were used for in vitro and in vivo analysis. Bioinformatic molecular docking prediction and following validation by surface plasmon resonance (SPR) technology, cellular thermal shift assay (CETSA), and isothermal titration calorimetry (ITC) were conducted to explore the binding between ginsenoside Rg5 and 90 kD heat shock protein alpha (HSP90α). The effects of ginsenoside Rg5 on HSP90-cell division cycle 37 (CDC37) interaction, the client protein stability, and the downstream regulations were further explored. Results showed that ginsenoside Rg5 could induce cell-cycle arrest at the G1 phase and enhance irradiation-induced cell apoptosis. It could bind to HSP90α with a high affinity, but the affinity was drastically decreased by HSP90α Y61A mutation. Co-immunoprecipitation (Co-IP) and ITC assays confirmed that ginsenoside Rg5 disrupts the HSP90-CDC37 interaction in a dose-dependent manner. It reduced irradiation-induced upregulation of the HSP90-CDC37 client proteins, including SRC, CDK4, RAF1, and ULK1 in A549 cell-derived xenograft (CDX) tumors. Ginsenoside Rg5 or MRT67307 (an IKKε/TBK1 inhibitor) pretreatment suppressed irradiation-induced elevation of the LC3-II/β ratio and restored irradiation-induced downregulation of p62 expression. In A549 CDX tumors, ginsenoside Rg5 treatment suppressed LC3 expression and enhanced irradiation-induced DNA damage. In conclusion, ginsenoside Rg5 may be a potential radiosensitizer for lung adenocarcinoma. It interacts with HSP90α and reduces the binding between HSP90 and CDC37, thereby increasing the ubiquitin-mediated proteasomal degradation of the HSP90-CDC37 client proteins.